Agile Transformation of the Russian Sector of Economy According to the Legislative Framework - BALASHOVA, Elena S.; GROMOVA, Elizaveta A. (Journal of Advanced Research in Law and Economics, 2017)
The development of the world community corresponds to the onset of the Fourth Industrial Revolution. It is a qualitatively new stage of development. Fundamental changes are expected in the economic sphere. Agile is a new but extremely suitable management model that can counteract such problems as uncertainty and high speed of business environment change. A number of features of an agile approach are highlighted. Agile transformation as a necessary stage of development is considered. The state of the legal environment of Russia in the context of agile transformation is analyzed. Examples of measures that stimulate transformation in the telecommunications industry and the banking industry in Russia are given. Russian sector of economy is at the beginning of the road of radical changes and is on the verge of transition to a new stage of development – to the information society and integration into the global information space. The conclusion about the rationality of introducing the agile approach with a view to improving the efficiency of all branches of the national economy is made.